2016
DOI: 10.1097/sla.0000000000001896
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Versus Total Parenteral Nutrition in Patients Undergoing Pancreaticoduodenectomy

Abstract: In patients undergoing PD, NJEEN was associated with an increased overall postoperative complications rate. The frequency and the severity of POPF were also significantly increased after NJEEN. In terms of safety and feasibility, NJEEN should not be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 43 publications
3
67
1
4
Order By: Relevance
“…In this issue of Annals of Surgery, Perinel et al demonstrated contrasting results to those of previous studies that reported the benefits of EEN in patients undergoing PD (10). This was a prospective, multicenter, and randomized controlled trial involving 204 patients (age, >18 years) undergoing PD at nine French institutions.…”
contrasting
confidence: 40%
“…In this issue of Annals of Surgery, Perinel et al demonstrated contrasting results to those of previous studies that reported the benefits of EEN in patients undergoing PD (10). This was a prospective, multicenter, and randomized controlled trial involving 204 patients (age, >18 years) undergoing PD at nine French institutions.…”
contrasting
confidence: 40%
“…A total of 51 articles were utilized for the review, with 14 addressing malnutrition and pancreatic dysfunction at pancreatic cancer diagnosis [13,14,15,16,17,18,19,20,21,22,23,24,25,26]; 19 addressing pancreatic dysfunction after surgery [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45], including 10 which also discussed preoperative dysfunction and nutrition [27,30,31,32,33,35,37,39,40,41]; and 18 addressing nutritional intervention [11,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62] (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Postoperative therapy with other somatostatin analogs has not been shown to be effective [38]. Postoperative total parenteral nutrition also reduces the fistula rate compared to early postoperative nasojejunal enteral nutrition [31]. The value of the omission of intraoperative drain placement is currently unclear: It reduced the pancreatic fistula rate in one multicenter trial [39] but led to an increase in morbidity and mortality in another study [40].…”
Section: Prevention Of Postoperative Pancreatic Fistulamentioning
confidence: 99%
“…The nationwide perioperative mortality rate was even higher (7.7%) and did not improve between 2009 and 2013 [30]. The high perioperative mortality is associated with a morbidity of up to 50%, mostly due to procedure-related complications [31]. While anastomotic leakage of the biliary and gastrointestinal anastomosis is exceedingly rare, leakage of the pancreatic anastomosis, i.e.…”
Section: Introductionmentioning
confidence: 99%